Mitologi Representation Dewa Indra in Pandage War at Usaba Waste Ceremony in the Tenganan Traditional Village Pegringsingan Manggis, Karangasem, Bali (Social Theological Perspective) - I Nyoman Subamia; I Made Suastika; I Nyoman Linggih (Sociological Jurisprudence Journal, 2021)
Pandan war is one of the important ceremonies and obligatory ceremonies called Usaba Sambah in the people of Tenganan Pegringsingan to God in manifestation as Dewa Indra. To raise three problems, namely (1) the form of pandan war , (2)axiology of theology social of pandan war, and (3) the implications of pandan war.This study carried out qualitatively, so that data analysis was carried out in a qualitative and interpretative descriptive manner. By using research methods, such as participatory observation, interviews, literature studies, and documentation studies. The results showed that: (1) The process of pandan war was one of the most important and obligatory parts of the religious ceremony in the Usaba Sambah ceremony in Tenganan Pegringsingan Village (2) The axiology of social theology in pandan war is (a) pandan war as a form of worship; (b) pandan war as a life learning process; (c) pandan war as a pattern of social interaction; (d) pandan war as a defense of religious traditions; and (e) the pandan war as a show of the ancient warrior knight. (3) the implication of pandan war in the usaba sambah ceremony is (a) increasing the Å›raddhÄ and the devotion of the peregraningan community; (b) fostering a sense of togetherness between low income communities; (c) strengthen in maintaining the local historical genius; (d) the interaction of communication between communities is established; (e) applying the value of ancestral heritage as a living foundation; and (f) pandan war as the development of cultural tourism destinations. The research findings are as follows. From the perspective of religious theory, the symbol system used in pandan war is maintained especially the concept of pingit (secret). The concept of pingit in pandan war is when the pesangkepan is not allowed to pray / spells known by anyone other than pemangku. In this case, it should only be known by the designated party only. From the perspective of the value theory, it was found that the pandanus war is a sacred dance of offerings, which should not be danced by others which is only carried out on pandanus war on the first day at Bale Petemu Kaja and not in any place. Based on symbolic interaction theory, a shift in meaning of pandan war arises from social interaction between local communities, shifting to global community interaction through warfare on the second day as a venue for tourism promotion in modern tourism contractions. There are other people (not the Tenganan people) who also participated in many pandan wars on the stage performance.